Measures used to quantify participation in childhood disability and their alignment with the family of participation‐related constructs: a systematic review. (19th July 2018) - Adair, Brooke; Ullenhag, Anna; Rosenbaum, Peter; Granlund, Mats; Keen, Deb; Imms, Christine
Abstract : Aim: We aimed to identify measures used to assess the participation of disabled children and to map the measures' content to the family of participation‐related constructs (fPRC) to inform future research and practice. Method: Six databases were searched to identify measures used to assess participation in health, psychology, and education research. Included studies involved children aged 0 to 18 years with a permanent impairment or developmental disability and reported use of a quantitative measure of participation. A second search sought relevant literature about each identified measure (including published manuals) to allow a comprehensive understanding of the measure. Measurement constructs of frequently reported measures were then mapped to the fPRC. Results: From an initial yield of 32 767 articles, 578 reported one or more of 118 participation measures. Of these, 51 measures were reported in more than one article (our criterion) and were therefore eligible for mapping to the fPRC. Twenty‐one measures quantified aspects of participation attendance, 10 quantified aspects of involvement as discrete scales, and four quantified attendance and involvement in a manner that could not be separated. Interpretation: Improved understanding of participation and its related constructs is developing rapidly; thoughtful selection of measures in research is critical to further our knowledge base. What this paper adds: The fPRC can support our rapidly evolving and expanding understanding of participation. Instruments selected to measure participation do not always align with emerging concepts. Matching research aims to a chosen measure's content will improve understanding of participation. Opportunities exist to develop validated participation measures, especially self‐reported measures of involvement. What this paper adds: The fPRC can support our rapidly evolving and expanding understanding of participation. Instruments selected to measure participation do not always align with emerging concepts. Matching research aims to a chosen measure's content will improve understanding of participation. Opportunities exist to develop validated participation measures, especially self‐reported measures of involvement. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.